2016
DOI: 10.1108/ci-09-2015-0047
|View full text |Cite
|
Sign up to set email alerts
|

Information technology and safety

Abstract: Purpose The architecture, engineering and construction industry is known to account for a disproportionate rate of disabling injuries and fatalities. Information technologies show promise for improving safety performance. This paper aims to describe the current state of knowledge in this domain and introduces a framework to integrate attribute-level safety risk data within existing technologies for the first time. Design/methodology/approach The framework is demonstrated by integrating attribute safety risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Moreover, the experimental results from real-world environment show that the proposed site-specific model can improve the positioning accuracy of general models from the state-of-the-art. The tool, available open-source, is modular and extensible through plug-ins allowing to model building systems with different requirements In the work [17], we can find a complex framework, which integrate attribute-level safety risk data within existing technologies for the first time. The framework is demonstrated by integrating attribute safety risk data with information retrieval, location and tracking systems, augmented reality and building information models.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the experimental results from real-world environment show that the proposed site-specific model can improve the positioning accuracy of general models from the state-of-the-art. The tool, available open-source, is modular and extensible through plug-ins allowing to model building systems with different requirements In the work [17], we can find a complex framework, which integrate attribute-level safety risk data within existing technologies for the first time. The framework is demonstrated by integrating attribute safety risk data with information retrieval, location and tracking systems, augmented reality and building information models.…”
Section: Resultsmentioning
confidence: 99%
“…Irizarry et al [134] also revealed that the supply chain is arranged in a better precise, efficient, and cost-effective method with the integration of BIM and geographic information systems (GIS). From the perspective of safety management and planning, through BIM 4D's simulation and visualization of the green building construction progress, BIM can conduct risk identification and safety training for management personnel and construction workers [135][136][137][138][139]. Moreover, through the BIM 4D hazard identification component established by Heidary et al [140], BIM can assist green building construction managers in identifying and demonstrating the potential construction hazards in the early stages of green building projects [140].…”
Section: Planning and Schedule Management Optimizationmentioning
confidence: 99%
“…This method enhances the predictability of construction and transforms the traditional pattern of construction plans [100]. By simulating the construction progress and potential construction accidents, personnel training and safety education can be provided by BIM utilization [135,136,144]. Nicał and Wody ński [129] put forward that the impact of construction activities on the surrounding environment can be simulated through BIM 6D, which is necessary to support green buildings to conform to specific green building evaluation standards.…”
Section: Planning and Schedule Management Optimizationmentioning
confidence: 99%
“…The following terms are how scientific papers referred to the idea of PtD: • Prevention through Design (PtD) (Ferrante, 2010;Hallowell et al, 2016;Karakhan & Gambatese, 2017;Kasirossafar & Shahbodaghlou, 2013b;Toole & Carpenter, 2013); • Design for Safety (DfS) Lee et al, 2020;Mering et al, 2017); • Safety in Design (Horberry, 2014;Li et al, 2020;Taiebat et al, 2012); • Design for Occupational Safety and Health (DfOSH) (Manu et al, 2019;Poghosyan et al, 2020); • Design Risk Management (Harvey et al, 2019;Mesaros et al, 2019).…”
Section: Engineering Management In Production and Servicesmentioning
confidence: 99%